HISTORY OF STUDY OF SOURCES OF URBAN CULTURE OF BUKHARA EMIRATE - Atamirzayeva Munavvar Abdurashid qizi (Scholar Express Journal, 2024)
In this article, the source studies of the history of urban culture of the Bukhara Emirate, their analysis in terms of groups, and the extent to which the culture of the Bukhara Emirate has developed in the works of scientists are discussed.
Keywords: sources; historical monuments; khans